The ins and outs of secretion from pancreatic beta-cells: control of single-vesicle exo- and endocytosis. - MacDonald, P; Rorsman, P (2007)
Exocytosis of insulin-containing secretory vesicles in pancreatic beta-cells is crucial to maintenance of plasma glucose levels. They fuse with the plasma membrane in a regulated manner to release their contents and are subsequently recaptured either intact or through conventional clathrin-mediated endocytosis. Here, we discuss these mechanisms in beta-cells at the single-vesicle level.